Howland current source design criteria (2007)
It is presents the theoretical analysis of the source of Howland current with the purpose of providing a criterion forthe selection of the passive and active components that confonn it. The methodology to study the Howland currentsource are divided in fourth parts, first, the circuit is analyzed over ideal conditions, ideal operational amplifier.Second, the finite open loop gain and finite band wide effects are studied. Third, sorne design criteria to design aHowland current source are detennined and explained. Finally, a numerical example with anAnalog Device amplifieris presented.